Assessment of trochanteric osteotomy fragment union after acetabular fracture surgery. Issue 2 (February 2017) - Dubina, Andrew G.; Wickramaratne, Niluka; O'Toole, Robert V.; Manson, Theodore T.
Abstract: Background: Trochanteric osteotomies are performed in conjunction with standard approaches to improve surgical exposure during open reduction and internal fixation (ORIF) of acetabular fractures. The literature on total hip arthroplasty reports nonunion rates as high as 30% associated with trochanteric osteotomies; however, few data exist regarding the outcomes of trochanteric osteotomies for acetabular fracture surgery. Our hypotheses were 1) patients receiving trochanteric osteotomies during ORIF of acetabular fractures have a low rate of nonunion of the osteotomy fragment, and 2) hip abduction precautions are not necessary with digastric type osteotomies. Patients and methods: A retrospective review was conducted to identify patients with acetabular fractures between July 2002 and June 2010 (n = 734 fractures) who required trochanteric osteotomies (n = 64, 9% of fractures). Forty-seven met inclusion criteria of adequate follow-up (>56 days). No excluded patient experienced a complication. Fractures were classified using the Letournel-Judet classification system. Results: Only seven (20%) of 35 patients who received digastric osteotomies had hip abduction precautions applied during the postoperative period. All study patients were shown to have radiographic union at the trochanteric osteotomy site (100% union rate, n = 47). Hip abduction precautions intended to protect the osteotomy site and reduce the risk of nonunion and fixation failure were infrequently applied to patients with digastric osteotomies (20%) in this cohort. Multiple protective factors against nonunion were present in this study population compared with previous arthroplasty studies from other institutions. Conclusions: Trochanteric osteotomies are not associated with a significant nonunion rate, and digastric osteotomies might be safely managed without hip abduction precautions.